VCA-DCV VMware certified associate on vSphere study guide VCAD-510 - Schmidt, Robert (Sybex, 2015)
Use this expert guide to prepare for the VCA-DCV exam. VCA-DCV VMware Certified Associate on vSphere Study Guide: VCAD-510 is a comprehensive study guide for the VMware Certified Associate - Data Center Virtualization exam. Hands-on examples, real-world scenarios, and expert review questions cover the full exam blueprint, and the companion website offers a suite of tools to help you prepare for the exam including practice exams, electronic flashcards, and a glossary of key terms. In addition, the website includes videos that demonstrate how to complete the more challenging tasks. Focused on practical skills, this study guide not only prepares you for the certification exam, but also for the duties expected of a VCA. The VMware Certified Associate-Data Center Virtualization certification targets those with limited virtualization and VMware data center technology experience, providing a springboard to the popular VMware Certified Professional-Data Center Virtualization certification. Virtualization has become a high priority among organizations, and credentialed professionals are in high demand. This guide helps you prove a certain level of foundational skill in basic virtualization technology, including the vSphere suite's Infrastructure Services, Application Services, and vCenter Server. Topics include: -Explaining data center virtualization concepts -Identifying the core components of vSphere -Networking and storage planning/configuration with vSphere -Correlating VMware solutions to common business challenges. The VCA-DCV certification is the only one with no instructor-led training requirement, so a thorough study guide is an invaluable tool in you exam preparation. This book not only covers the full exam, but also provides practice designed to actually improve the skills used every day on the job. VCA-DCV VMware Certified Associate on vSphere Study Guide is more than just test prep--it's job prep.
Title from resource description page (Recorded Books, viewed December 21, 2015)
Keywords: Computers; Electronic digital computers; Ordinateurs; computers; COMPUTERS; Certification Guides; General